2021
DOI: 10.3390/nano11092287
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Berry Quality and Antioxidant Potential of Flame Seedless Grapes by Foliar Application of Chitosan–Phenylalanine Nanocomposites (CS–Phe NCs)

Abstract: The production and sustainability of grape berries with high quality and health-promoting properties is a major goal. In this regard, nano-engineered materials are being used for improving the quality and marketability of berries. In this study, we investigated the potential role of chitosan–phenylalanine nanocomposites (CS–Phe NCs) in improving the quality of Flame Seedless (Vitis vinifera L.) grape berries, such as titratable acidity (TA), pH, total soluble solids (TSS), ascorbic acid, total phenolics, total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 51 publications
2
21
0
Order By: Relevance
“…In this sense, Sohail et al [22] reported that postharvest Arg treatment prevented postharvest senescence of broccoli by reducing the ascorbic acid content and enhancing the antioxidant capacity. Likewise, the foliar application of CTS-phenylalanine nanocomposites at 5 mM concentration enhanced ascorbic acid content in grape fruit [52]. Babalar et al [24] reported that the higher ascorbic acid accumulation in pomegranate fruit treated with arginine resulted from higher GR/ APX system activity or lower AAO enzyme activity and remarkably assisted to increasing the antioxidant capacity of fruits during cold storage at 4 °C for 60 days.…”
Section: Ascorbic Acid Content and Dpph Scavenging Capacitymentioning
confidence: 98%
“…In this sense, Sohail et al [22] reported that postharvest Arg treatment prevented postharvest senescence of broccoli by reducing the ascorbic acid content and enhancing the antioxidant capacity. Likewise, the foliar application of CTS-phenylalanine nanocomposites at 5 mM concentration enhanced ascorbic acid content in grape fruit [52]. Babalar et al [24] reported that the higher ascorbic acid accumulation in pomegranate fruit treated with arginine resulted from higher GR/ APX system activity or lower AAO enzyme activity and remarkably assisted to increasing the antioxidant capacity of fruits during cold storage at 4 °C for 60 days.…”
Section: Ascorbic Acid Content and Dpph Scavenging Capacitymentioning
confidence: 98%
“…Similarly, several reports described the synthesis of CHNPs with a size of 50−100 nm using the same procedure (Abdel‐Rahman et al., 2021; Karimirad et al., 2019; Mohammadi et al., 2015a; Valizadeh et al., 2021). The ionic gelation method allowed the formation of CHNPs with spherical shapes (Figure 1b) (Gohari et al., 2021; Karimirad et al., 2018; Lustriane et al., 2018). On the other hand, a few reports used the nanoprecipitation method using a peristaltic pump for the preparation of the CHNPs (Hernandez‐Lopez et al., 2020).…”
Section: Characteristics Of Chnpsmentioning
confidence: 99%
“…(a) Transmission electron microscopy (TEM) images and size distribution of CHNPs synthesized using the ionic gelation method (Cuong et al., 2022). (b) Scanning electron microscopy (SEM) and TEM analyses of chitosan–phenylalanine NPs (Gohari et al., 2021). (c) TEM images of CHNPs and starch/CHNPs films (Shapi'i et al., 2020).…”
Section: Characteristics Of Chnpsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Egypt, it is ranked second after citrus fruits, due to its high net return; it is grown rapidly, especially in reclaimed soils [ 6 , 7 ]. Due to the availability of antioxidants, minerals (such as calcium, magnesium, and iron), soluble sugars, anthocyanins, flavonoids, organic acids, vitamins (such as B1, B2, and C), and aromatic compounds, the grapevine is one of the most economically significant sources for the human health and food industries [ 8 , 9 , 10 , 11 ]. Furthermore, the grapevine has rich phenolic compounds, so it has positive health effects on people to protect them from different diseases [ 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%